Analysis and diagnosis of the instability affecting "La Bonita" area, Amagá, Antioquia, Colombia. (2015)
In the “La Bonita” sector (Amagá, Antioquia), between km 3+200 and km 3+500 of the Camilo C. Restrepo (Amagá) – El Cinco (Fredonia) road, which is above the rocks of the upper member of the Amagá formation (conformed mainly by interbedded claystones, sandstones and thin beds of coal), occur many instability processes that seriously affect the infrastructure of the area, and could be the result of the variations of mechanical and mineralogical properties of the claystones by effect of humidity fluctuations in the study area. According to the results obtained after multiple field trips, mapping of morphodynamic processes, subsoil explorations and laboratory tests, was determined that these materials, even as a rock, given their particular characteristics, have the ability to expand (changing their volume by about 10%) upon contact with water, generating expansion pressures up to 700kPa on the overlying materials, leading to the development of multiple slow morphodynamic processes (whose rate is related to winter seasons) that destabilize the ground.